Workflow Modelling and Analysis Based on the Construction of Task Models - Glória Cravo (The Scientific World Journal)
We describe the structure of a workflow as a graph whose vertices represent tasks and the arcs are associated to workflow transitions in this paper. To each task an input/output logic operator is associated. Furthermore, we associate a Boolean term to each transition present in the workflow. We still identify the structure of workflows and describe their dynamism through the construction of new task models. This construction is very simple and intuitive since it is based on the analysis of all tasks present on the workflow that allows us to describe the dynamism of the workflow very easily. So, our approach has the advantage of being very intuitive, which is an important highlight of our work. We also introduce the concept of logical termination of workflows and provide conditions under which this property is valid. Finally, we provide a counter-example which shows that a conjecture presented in a previous article is false.